Different Representations of the Blueberry in Romanian Philately, 1964-2022 - Bogdan-Vasile Cioruta; Alexandru Leonard Pop; Mirela Coman (Current Topics in Agricultural Sciences Vol. 6, 2022)
Forest products play a vital role in our lives in many ways we can imagine. Berries, for example, are still an important source of food, being of real use in defining a healthy diet and natural medicine. But does blueberry have other roles at the community level? Can the blueberry be viewed from another perspective? Here are some questions we aim to answer. In this context, to show that there have been and still are concerns regarding the highlighting of the role of berries in the community, the present study is proposed to analyze their entire Romanian philatelic history. The purpose of this paper was to see and look at the extent to which Romanian philately illustrates and promotes berries as part of ecosystem products and services, but especially blueberries. As such, the first approach is limited to the philatelic appearances of the blueberry (postage stamps, “first day of issue” envelopes, maximum postcards, occasional envelopes), appearances identified within the various platforms with philatelic content. The identified philatelic pieces for the reference period 1964-2022, show that there have been and are concerns for the promotion of a healthy diet, a diet that can be thought of in a balanced way by including the consumption of berries, including blueberries.